Granulomatous lobular mastitis in pregnancy: report of 29 cases - Liang, Hongyi; Shi, Guangxi; Chen, Hanhan; Liu, Xiaofei; Zhang, Zhe; Song, Aili; Li, Jingwei (Frontiers in Oncology, 2025)
Granulomatous lobular mastitis (GLM) is a rare inflammatory breast disease, and there are few reports of GLM in pregnancy (GLMIP). Therefore, this study retrospectively analyzed cases diagnosed with GLMIP from 2011 to 2023 and found that in patients with GLMIP there were varied demographic manifestations such as age, pregnancy weeks, and numbers of pregnancy and delivery, and several associated complications including erythema nodosum, arthritis and lower extremity edema. Among them, 82.8% of the patients received integrated traditional Chinese medicine (TCM) and western medicine treatment, and 17.2% of the patients received TCM treatment alone, but the application rate of TCM treatment was 100%. The results showed that both groups significantly improved the effective rate (91.7% and 60.0%, respectively), improved breast appearance (4.1% and 20.0%, respectively), reduced the rate of progression or recurrence rate (8.3% and 60.0%, respectively), and shortened the time for complete remission (13.793 months vs 12.625 months, respectively). To date this study is the one with the largest sample size of GLMIP, but also the one with the largest sample size in which the combination of TCM treatment and non-surgical treatment was applied. The complications include erythema nodosum, arthritis and lower extremity edema. Therefore, the application of TCM in the treatment of GLMIP is worth promoting vigorously.